2017
DOI: 10.1002/mus.25971
|View full text |Cite
|
Sign up to set email alerts
|

Ocular presentation of myasthenia gravis: A natural history cohort

Abstract: As patients were steroid-naive before generalization, our cohort approximated the natural history of the condition. Muscle Nerve 57: 622-627, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 21 publications
6
26
3
Order By: Relevance
“…Given that older age at onset has been demonstrated to correlate with higher risk of generalization [16,17], the lower conversion rate in this study than in Caucasian population further highlights the potential role of ethnicity in the prevalence of OMG. Several studies suggested that factors such as age at onset, AChR-Ab titers, positive rate of RNS, thymoma and immunosuppressive therapy were associated with generalization [6][7][8][9].…”
Section: Predictors Of Conversion To Gmgmentioning
confidence: 60%
See 1 more Smart Citation
“…Given that older age at onset has been demonstrated to correlate with higher risk of generalization [16,17], the lower conversion rate in this study than in Caucasian population further highlights the potential role of ethnicity in the prevalence of OMG. Several studies suggested that factors such as age at onset, AChR-Ab titers, positive rate of RNS, thymoma and immunosuppressive therapy were associated with generalization [6][7][8][9].…”
Section: Predictors Of Conversion To Gmgmentioning
confidence: 60%
“…Prior studies showed that the conversion rate of juvenile-onset OMG fluctuated between 23 and 43% [3,21], while that of adultonset OMG between 31 and 49% [4,22]. Kamarajah and Wang reported that late-onset was correlated with higher risk of generalization [16,17]. In another study, patients were inclined to convert to GMG with increasing age at onset [2].…”
Section: Predictors Of Conversion To Gmgmentioning
confidence: 99%
“…In light of this, several studies have tried to identify risk factors of secondary generalization to avoid unnecessary adverse effects caused by immunosuppressive medications (9,10,14,15). Thus far, however, it has been challenging to stratify patients with OMG into subgroups with different risk levels of secondary generalization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying the predictors of CSR after thymectomy might be beneficial and may allow us to better counsel patients about formulating a treatment plan. A l t h o u g h v e r y f e w s t u d i e s h a v e s p e c i f i c a l l y investigated the role of thymectomy in OMG, a metaanalysis of 26 studies with a median eligible sample size of 16 (range, 3-105) showed that thymectomy is beneficial in terms of inducing remission in patients with OMG (9). Of these studies, one with a sample size of 61 patients demonstrated that thymectomy could lead to an apparent cure (symptoms free without medications) in 51% of patients with OMG (16).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported the conversion rate of juvenile-onset OMG patients fluctuated between 23% and 43% [3,17], while that of adult-onset OMG patients fluctuated between 31% and 49% [4,18]. Kamarajah and Wang suggested late-onset were positively related with generalization [19,20]. Mark et al [2] also reported patients were inclined to converted to GMG with increasing onset age.…”
Section: Discussionmentioning
confidence: 99%